Association between continuous decrease of plasma VEGF-A levels and the efficacy of chemotherapy in combination with anti-programmed cell death 1 antibody in non-small cell lung cancer patients. (2020) - Tozuka, Takehiro; Yanagitani, Noriko; Sakamoto, Hiroaki; Yoshida, Hiroshi; Amino, Yoshiaki; Uematsu, Shinya; Yoshizawa, Takahiro; Hasegawa, Tsukasa; Ariyasu, Ryo; Uchibori, Ken; Kitazono, Satoru; Seike, Masahiro; et al.
Abstract: Objectives: Vascular endothelial growth factor-A (VEGF-A) plays important roles in tumor immune suppression and thus correlates with the efficacy of anti-programmed cell death-1/ligand 1 (anti-PD-1/PD-L1) antibodies. We aimed to determine the association between change in plasma VEGF-A levels and the efficacy of chemotherapy combined with anti-PD-1/PD-L1 antibodies (chemo-PD1) in non-small cell lung cancer (NSCLC) patients. Methods: We included NSCLC patients treated with chemo-PD1. Plasma VEGF-A levels were measured at baseline (Pre) and days 7 (D7) and 14 (D14) after the initiation of chemo-PD1. Continuous VEGF-A decrease was determined by comparing Pre with the median value of maximum change rate of posttreatment VEGF-A as cutoff. Patients whose change rates of VEGF-A at both D7 and D14 were consistently lower than the cutoff value were classified into the VEGF-A decrease group, whereas those whose VEGF-A at D7 or D14 were higher than the cutoff level were classified into the VEGF-A no-decrease group. The primary outcome was progression-free survival (PFS). Results: A total of 32 patients were evaluated. The median Pre VEGF-A levels was 49 (range, 13–257). The median change rate of VEGF-A at D7 and D14 was -25.6% (range, -77.5–376.9) and -42.3% (range, -100–138.5) respectively. The cutoff value of posttreatment VEGF-A change rate was -9.3%. The PFS was significantly longer in the VEGF-A decrease group than that in the VEGF-A no-decrease group (median, not reached vs 2.4 months; p  = 0.017). Conclusions: Continuous decrease of plasma VEGF-A levels during treatment may be associated with the efficacy of chemo-PD1.